Sistem Pelaksanaan Penyimpanan Rekam Medis di Kilinik Pratama Bakti Timah Pangkalbalam - Sari Wahyuni (Syntax Corporation Indonesia, 2021)
The medical record contains records and documents about the patient’s identity,examination,treatment,action,and other service that have been provided o the patient. Implementation of retrieval the patients medical record in clinic Pratama Bakti Timah pangkalbalam not using Tracer using KIB(patient identity card)causes medical record difficult to find and not neat become medical record was not found (missfile). Objective to xamine how imlementation filing systems for medical record in Clinic Pratama Bakti Timah Pangkalabalam. The research was conducted using a descriptive is a method that is carried out by descriptive an situation objective. Implementation of the retrieval and filling system of medical record was not using tracer.based on location of medical record filling was using a centralization system and filling system of medical record was was unit numbering system.haven’t procedureof the implementation of falling system.There are one officers responsible for the filling of medical record.Medical record folder in Klinik Pratama Bakti Timah Pangkalbalam has not found a place to write a column for the last visit of examination or treatment. Medical record folder are also easy to ripped and form of medical record folder does not help officers looking for medical record. Filing of medical record shaped like a sorting rack. So, in this case, does not same with the shape of the medical record filing generally. There are several barrier in the implementation of family folder system of medical records of filing system include looking for old medical record, duplicate medical record number, medical record file is not found, and less of filing shelves